Work for your happiness - Theoretical and empirical study defining and measuring happiness at work - Suojanen, Ilona (fi=Turun yliopisto|en=University of Turku|, 2012)
There are vast changes in the work environment, and the traditional rules and management methods might not be suitable for today’s employees anymore. The meaning of work is also changing due to the younger and higher educated generations entering the markets. Old customs need to be re-validated and new approaches should be taken into use. This paper strongly emphasizes the importance of happiness research and happiness at work. The values towards the meaning of work are changing; people demand happiness and quality from all aspects of their lives. The aim of this study is to define happiness - especially at work - and to explain how it can be measured and what kind of results achieved. I also want to find out how the contents of work and the working environment might enhance happiness. The correlation between education and happiness is discussed and examined. I am aware that the findings and theories are concentrating mainly on Western Countries and highlighting the values and work-environments of those societies. The main aim of the empirical study is to find out if there are connections between happiness and work in data collected by World Value Survey in 2005, and if the profession has effects on happiness. Other factors such as the correlation of age, sex, education and income are examined too. I also want to find out what kind of values people have towards work and how these affect the happiness levels. The focus is on two nations: Finland (N=1014) and Italy (N=1012). I have also taken the global comparison within, that is all 54 countries (N=66,566) included in the 5th wave (during the years 2005 -2008) of the World Value Survey. The results suggest that people are generally happy around the world; happiness decreasing with the age, the educated being happier than the uneducated and the employed happier than the unemployed. People working in neat “white collar” jobs are more likely happier than those working in factories or outdoors. Money makes us happier, until certain level is reached. Work is important to people and the importance of work adds happiness. Work is also highly appreciated, but there are more happy people among those who do not appreciate work that highly. Safety matters the most when looking for a job, and there are more happy people among those who have selected the importance of work as the first choice when looking for a job, than among those to whom an income is the most important aspect. People are more likely happy when the quality of work is high, that is when their job consists of creative and cognitive tasks and when they have a feeling of independence.

Työmaailmassa on tapahtunut valtavasti muutoksia, eivätkä perinteiset käytänteet ja johtamismetodit välttämättä ole enää sopivia tämän hetken työpaikoille. Myös työn merkitys on muuttunut uuden, korkeasti koulutetun sukupolven myötä. Vanhat tavat tulisi arvioida uudelleen ja uudet käytänteet ottaa huomioon. Tämä tutkielma korostaa onnellisuuden tärkeyttä työssä. Työhön kohdistuvat arvot ovat muuttumassa ja ihmiset kaipaat onnellisuutta kaikilla elämän aloilla. Tutkimuksen tavoitteena on määrittää onnellisuus – erityisesti työssä – ja kartoittaa miten sitä voidaan mitata ja minkälaisia tuloksia on saatu. Haluan myös selvittää kuinka työn sisältö ja työympäristö vaikuttavat onnellisuuteen. Myös koulutuksen ja onnellisuuden välistä yhteyttä tarkastellaan. Olen tietoinen siitä, että teoriat ja löydöt perustuvat länsimaisiin näkemyksiin ja arvoihin. Empiirisessä osiossa haetaan yhteyttä onnellisuuden ja työn välillä World Value Surveyn vuonna 2005 keräämästä datasta. Ammatin, iän, sukupuolen, koulutuksen ja tulojen yhteyttä onnellisuuteen tarkastellaan myös. Haluan lisäksi selvittää minkälaisia arvostuksia ihmisillä on työtä kohtaan ja kuinka ne vaikuttavat onnellisuuteen. Tarkastelen kahta maata: Suomea (N=1014) ja Italiaa (N=1012). Myös kaikki 54 maata (N=66 566), jotka olivat mukana viidennessä tutkimuksessa vuosina 2005-2008, ovat mukana kansainvälisessä vertailussa. Tulosten mukaan ihmiset ovat melko onnellisia ympäri maailmaa; onnellisuuden vähentyessä iän myötä, koulutuksen lisätessä onnellisuutta ja työssäkäyvien ollessa onnellisempia kuin työttömien. Siistissä toimistotyössä oleva on todennäköisemmin onnellinen kuin tehdas- tai ulkotyöläinen. Raha tekee meistä onnellisempia tiettyyn rajaan asti. Työ on tärkeää ihmiselle ja tärkeys lisää onnellisuutta. Työllä on myös korkea arvostus, mutta ihmiset ovat todennäköisemmin onnellisia, kun he eivät arvota työtä kovin korkealle. Turvallisuus on tärkeintä työtä haettaessa, ja ihmiset ovat onnellisimpia kun työn sisältö on heille tärkeämpää kuin tulot. Työn laatu vaikuttaa onnellisuuteen: ihmiset ovat todennäköisesti onnellisempia kun heidän työtehtävänsä ovat monipuolisia ja vaativat luovuutta, sekä kun he kokevat itsenäisyyttä työssään.